Characterization of short time fluctuations in atmospheric wind speeds by LIDAR measurements - Matthias Wächter; A. Kühn Rettenmeier (Meteorologische Zeitschrift, 2009)
Wind velocity measurements were taken using a Leosphere Windcube LIDAR system, which operates as a pulsed laser Doppler anemometer. Here we report on first results, which show typical characteristics of atmospheric wind velocities. Especially pronounced intermittent (or heavy-tailed) probability density functions (PDF) of wind speed increments are present on all observed time scales. A transition for large time scales towards a more Gaussian shape is found if only ten minute intervals are selected which share the same mean wind speed. Both typical shapes of PDF are well described and modeled by two previously proposed models.